Snack Consumption among Iranian Children and Adolescents: The CASPIAN-IV Study - Maryam BAHREYNIAN; Mostafa QORBANI; Ramin HESHMAT; Mohammad Esmaeil MOTLAGH; Shirin DJALALINIA; Gelayol ARDALAN; Amir KASAEIAN; Fereshteh NAJAFI; Hamid ASAYESH; Bagher LARIJANI; Roya KELISHADI (Tehran University of Medical Sciences, 2015)
Background: This study aimed to assess the frequency of consuming different types of snacks among Iranian students according to socio-economic status (SES) of their living region. Methods: Data were obtained from the fourth national school-based surveillance survey entitled CASPIAN-IV study. Overall, 14880 school students, aged 6-18 years, were selected through multistage, cluster sampling from rural and urban areas of the of 30 provinces of Iran. The World Health Organization Global School Student Health Survey (WHO-GSHS) was used. Data were compared at national/sub-national levels by survey data analysis methods. Results: The participation rate was 90.6%, 13486 students (49.2% girls), mean (SD) age of 12.50 (3.36) years completed the study. At national level, fresh fruits were the most common used category of healthy snacks (55.74%, 95% CI: 54.51, 56.96). Boys had more daily consumption of milk (48.65% vs. 43.27%), and girls had more daily consumption of fresh fruits (58.07% vs. 53.47%). Urban residents had lower consumption of vegetables (30.53% vs. 37.55%), dried fruits (18.29% vs. 23.02%), and fresh fruits (45.33% vs. 50.09%) than their rural counterparts. Among unhealthy snacks, sweets had the highest daily consumption (34.15%, 95% CI: 33.04, 35.28). Boys had higher consumption of sweetened beverages (22.57% vs. 17.6%) and fast foods (3.51% vs. 2.17%). At national level, except than salty snacks (16.24% rural vs.11.83% urban), consumption of other junk snacks had no significant difference between urban and rural residents. Conclusion: Differences in the frequency of consuming healthy and unhealthy snacks according to the SES of the living region, and the choice differences between genders should be considered in planning national health programs.   Keywords: Snack, Healthy snack, Junk food, Socio-economic status, Iran